O17: HYALURONIC ACID DEPENDENT ADHESION IN COLORECTAL CANCER PERITONEAL METASTASIS. (27th April 2021) - Soliman, F; Ye, L; Jiang, W; Hargest, R
Abstract: Introduction: Peritoneal Metastasis (PM) in Colorectal Cancer (CRC) undoubtedly remains a challenge to treat and often portends a poor prognosis for patients. Hyaluronic acid (HA) is found throughout the body, including coating of the peritoneum. Interaction of HA with HA‐dependent adhesion molecules can facilitate cell adhesion within the peritoneum. HA may play a role in spread of PM in CRC in association with known HA‐receptor molecules CD44, RHAMM and ICAM‐1. Method: Expression of HA‐dependent and HA‐independent adhesion molecules were examined in CRC using tissue microarray datasets and matched to clinicopathological data.  In‐vitro  peritoneal modelling assessed cellular adhesion when treated with a competitive HA‐inhibitor (HAi) or excess exogenous HA. An  in‐vivo  Xenograft peritoneal model, using CD1 nude mice injected with CRC cells, were treated with either HAi or excess exogenous HA and compared to a control (PPL: PE9445FC2). Result: There is a significant increase in expression of HA‐dependent adhesion molecules seen in CD44, RHAMM and ICAM‐1 in CRC (p=<0.0001). Whilst Non‐HA‐dependent adhesion molecules demonstrated either significant downregulation or no expression difference. Cellular adhesion was decreased in three CRC cell lines when treated with HAi or excess HA. Treatment with HAi and HA  in‐vivo  confirmed a significant reduction in PM, compared to controls (HAi p=0.0094, HA p=0.0009). Conclusion: HA‐dependent adhesion molecules and HA appear to play a role in CRC. Targeting HA‐dependent interaction in CRC influences cellular adhesion and may have a potential therapeutic use in treatment of PM in CRC. Further in‐vitro and in vivo modelling is needed. Take‐home message: HA receptor adhesion molecules CD44, RHAMM and ICAM‐1 have all been independently implicated in adverse outcomes in colorectal cancer. Targeting HA receptor interaction appears to reduce peritoneal dissemination in colorectal cancer.